2012
DOI: 10.1039/c2jm30620d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and self-assembly of tetraphenylethene and biphenyl based AIE-active triazoles

Abstract: Self-assembly of fluorescent functional materials has attracted increasing interest in the fabrication of optoelectronic and biological nanodevices. Tetraphenylethene (TPE) is a typical dye molecule with aggregation-induced-emission (AIE) characteristics. Melding TPE carrying triple-bond functionality with diazide-containing biphenyl through ''click'' chemistry generates AIE-active luminogens [1,1 0biphenyl]-4,4 0 -diyl bis(6-(4-(4-(1,2,2-triphenylvinyl)phenyl)-1H-1,2,3-triazol-1-yl) hexanoate) [1(5)] and [1,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 98 publications
0
28
0
Order By: Relevance
“…Tang et al. showed that biphenyl‐based triazoles can also be used as a spacer for nanofiber formation . It should be noted that as the van der Waals forces bring the molecules together, other possible interactions may also occur between the self‐assembled molecules.…”
Section: Endowing Aie Molecules With Self‐assembly Ability Through Momentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al. showed that biphenyl‐based triazoles can also be used as a spacer for nanofiber formation . It should be noted that as the van der Waals forces bring the molecules together, other possible interactions may also occur between the self‐assembled molecules.…”
Section: Endowing Aie Molecules With Self‐assembly Ability Through Momentioning
confidence: 99%
“…[33] Ta ng et al showedt hat biphenyl-based triazoles can also be used as aspacer for nanofiber formation. [34] It should be noted that as the van der Waals forces bring the molecules together,o ther possible interactions may also occur betweent he self-assembled molecules. For example, p-p stacking may occur between benzene rings in the BTPE system,a nd the hydrophobic effect of the alkyl chains may contribute to the self-assembly of AIEgens with alkyl spacer chains.…”
Section: Self-assembly Of Aie Moleculesb Yc Ovalently Linking Amino Amentioning
confidence: 99%
“…[35,36] To expand the system,t he thiourea-linked chiral silole derivative 4 was synthesized by incorporatingc hiral phenylethanamine moieties onto the tetraphenylsilole unit. [37] Consideringt hat some achiral p-conjugated molecules can form helical assemblies through asymmetric packing of achiral building blocks, [38][39][40] we also prepared an achiral silole compound, hexaphenylsilole (HPS, 5)f or comparison. [41]…”
Section: Silole Derivativesmentioning
confidence: 99%
“…On the other hand, Zhang et al [36,37] have developed a number of covalent strategies for fabrication of AIE dyes containeing amphiphilic FONs through reversible addition-fragmentation chain-transfer (RAFT) polymerization and cross-linking. [38][39][40][41][42][43][44][45][46] However, most of these strategies still have some shortcoming. For example, most of commercially available amphiphilic compounds are expensive, and the obtained nanoprobes are often not stable when the concentration is lower than the critical micelle concentration (CMC).…”
Section: Introductionmentioning
confidence: 99%